Islamic Banking - Bláha, Jakub (2014)
The aim of this bachelor thesis is to introduce the Islamic banking. Describing historical and religious background of Islam, the Islamic banking and Shari'ah law. Then presenting financing techniques used in the Islamic banking. Eventually describing and analysing the Islamic banking in Malaysia. Comparison between the Islamic banking and the conventional banking is given throughout the bachelor thesis.